Pembrontakan terhadap pemerintahan yang sah (bugah) dalam perspektif hukum Islam - Sukring dan Rustam (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2016)
Islam is Rahmatan lil ‘Alamin religion, Islam loves peace and justice, Islam never teaches violence and corruption in the world. Along with global development and progress, the understanding of Islam teaching began to be degraded by some groups of Muslim, then came some groups that distort Islam religious teaching. There is a fundamental radical giving wrong interpretation to the religious teaching understanding. Then came terrorists and insurgents that against the legitimate government. Those who stay away from moderation will always cause the appearing of harsh and extreme groups in all time. The purpose of terrorists and insurgents is the destruction to the strength, power, stability, and safety of the nation. Hazard and press power of the insurgents against the government can not be tolerated. Because they commited treason against the legitimate government, the punishment for those who fight against Allah and his Messenger and who do mischief in the earth is killed and crucified or having their hands and feet cut in crossways, or exiled from his place. This article draws the condition of Muslim communities, especially in Islamic countries in the Middle East that are flaring up today.